Tema umetnosti in umetnika v romanih Plamenice in solze Andreja Blatnika in Dvanajst krogov Jurija Andruhoviča - Vollmaier Lubej, Janja (Jezik in slovstvo, 2017)
The article presents the theme of art and the artist in postmodernism, as applied to their changing role in a secularised, capitalist, consumer society. Two postmodern novels by significant authors, Blatnik's Torches and Tears and Andrukhovych's Twelve Circles, are used to demonstrate and illustrate some of the modifications discussed in a first part of the article.
Keywords: Blatnik, Andrej, 22. 5.1963-; "Plamenice in solze"; Andruhovyč, Jurij, 1960-; "Dvanajst krogov"; literarni motivi; postmoderna; postmodernizem; literarne študije; Slovene literature; slovenska književnost; ukrajinska književnost